Mensinkronkan Kurikulum Fakultas Tarbiyah Dan Ilmu Keguruan: Terhadap Regulasi/Kebijakan Pendidikan Nasional - Samlan Ahmad (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2016)
Curriculum development is an ongoing activity and process, including planing, improvement, implementation, and evaluation to anticipate  the latest development and demands. The Faculty of Islamic Education that prepares the graduates to be religious teachers, has been in recent years  required to fulfill the national policy of education. It will be insisted to review its curriculum in order to be synchronized and not ignores the characteristic of Islamic educaton. Improving the curriculum needs a clear frame of thought and work until producing the curriculum plan that will be implemented in actual curriculum. How to review and improve the curriculum? This paper answers this question and describes the theoretical and practical stages to improve the curriculum. It can be used as reference of  the department of religious education study in the Faculty of Islamic Education.